Relationship between health-related quality of life and self-esteem of adult patients receiving chemotherapy for cancer treatment - Ahmed, Sahar; Khalil, Shaymaa Sayed (International Journal of Advanced Nursing Studies, 2017)
Purpose: To identify the relation between self-esteem and health related quality of life of adult cancer patients receiving chemotherapy and to identify the demographic variables that may have impact on health related quality of life of cancer patients receiving chemotherapy.Methods: A cross-sectional, descriptive, correlational survey was utilized in this study. The study was conducted at the in-patient and out-patient clinic of oncology at South Egypt cancer institute. The sample consisted of 100 patients with the following inclusion criteria; adult patients diagnosed of any type of cancer, fully conscious and are willing to participate in the study. Two tools were used; 36-Item Short Form Health Survey Instrument and Rosenberg self-esteem questionnaire.Results: The majority of the studied sample (67 %) was female, their age ranges from 40 years and above, they were not working and were having a breast cancer (38%), there was a highly statistical significant difference in total HRQoL score and breast and lung cancer diagnosis.Conclusion: A quarter of the studied sample was having a satisfactory quality of life while near the entire studied sample were having a good self-esteem. Age, sex and occupation were socio-demographic variables that have impact on patient's quality of life.